Methodology Based on Critical Reflective Dialogue to Optimize Educational Leadership - Sofía Gamarra-Mendoza; José Gregorio Brito-Garcías (Education Sciences, 2025)
For educational leadership that promotes equity, there is evidence of successful leadership practices developed by educational leaders striving for social justice, such as the one planned by Leithwood. Furthermore, training programs for educational leaders seeking to replicate these practices have been dominated by training that encourages educational leaders to focus on learning outcomes without developing a critical–reflective dialogue with the school context, the diversity of educational institutions, and, consequently, with students and their families. In this sense, the objective of the research is to examine the interaction between community members such as directors, teachers and parents in eight educational institutions in the Peruvian jungle and propose a formative theoretical model based on critical and reflective dialogue, based on a review of various theories that have contributed to the formation of a dialogue grounded in indignation and questioning of the context. The methodology follows a mixed approach, with a sample of 136 teachers and 16 key informants, using a validated questionnaire and an in-depth interview as instruments. Data analysis showed low interaction between educational leaders and the community, a disconnect with the curricula, and a low sense of responsibility and commitment, reflected only in administrative compliance. Based on these results and the bibliographic review of general and specific theories, a theoretical model based on critical and reflective dialogue was designed to develop awareness and sensitivity toward education with social justice, for the development of successful educational leadership practices.